Distribuição Espacial de Anticarsia gemmatalis Hübner, 1818 (Lepidoptera: Erebidae) em soja utilizando Geoestatística - Nunes, Eduardo Lima [UNESP] (2016)
Soybran is one of the most important crops in Brazil, accounting for 49% of the planted area of grains in the country, and has shown growth as its production for each year. Among the most important pests of culture is the velvetbean-caterpillar, Anticarsia gemmatalis Hübner, 1818 (Lepidoptera: erebidae), responsible for up to 100% defoliation. So that the control is satisfactory, management techniques should be developed based on knowledge of the behavior of pests in the field, as their spatial distribution, for example. Methods such as geostatistical are efficient for the development of mapping a plague or natural enemy in the culture, and complements the integrated management strategies pest, with great potential for application to the study of insect behavior. The objective of this study was to evaluate the spatial distribution of velvetbean-caterpillar using geostatistics techniques in a planted area with grow crops M 7908 RR during the 2014/2015 in FCAV/UNESP Jaboticabal - SPwith 0,8 hectare, divided into 80 plots of 100 m² ( 10 mx 10 m). In each plot were examined at random five sampling points weekly through technical beat cloth on 2 meters during the vegetative and reproductive stages of culture. The geostatistical analysis allows the elaboration of experimental semivariogram, with adjustment of mathematical models in order to study the spatial dependence of the pests in the study area . It was observed that the soybean-caterpillar varies its population when there are high temperatures and almost no precipitation, which may be related to bad weather conditions for the onset of entomopathogenic fungi, making this fluctuation during the sampling dates when instead of maintaining a steady decline, increase at a time when there are those above conditions dry and hot weather. The caterpillar behaves in aggregate, a fact evidenced by the apparent existence of spatial dependence with a range varying from 7 to 55,42 m. In the samples with low infestation, could not verify the existence of spatial dependence.